Cultural Intermediaries’ Contribution To The Public Relations Behaviour In Educational Institutions At Slope Of Mountain Area - Ummi Hani'; Akmal Mundiri (Institut Agama Islam An-Nawawi Purworejo, 2023)
Public Public relations behaviour in educational institutions plays a very important role in maintaining communication between institutions and related stakeholders. However, some educational institutions do not understand the duties and functions of public relations. Public relations should also understand the expectations of institutional stakeholders around educational institutions. Understanding the cultural characteristics of society has a major contribution to the behaviour of institutional public relations. This research was conducted to understand the contribution of culture to public relations behaviour in educational institutions in the mountainside area, precisely in the Situbondo district. Qualitative methods were used in this research with a case study approach. Data were collected through observation, in-depth interviews, and documentation. Data analysis was carried out using data validity techniques of triangulation and extended observation. Based on the results of the research in the mountainside area, there are several cultures that influence the behaviour and PR strategies in the institution. these cultures include the sowan tradition, local communication patterns, door-to-door approach, and rewarding. This research is expected to provide a rich and comprehensive perspective on the contribution of cultural intermediaries to PR behaviour in educational institutions, especially mountain slope institutions.